Oceanographic Research. - WOODS HOLE OCEANOGRAPHIC INSTITUTION MASS (1949)
This report contains a quarterly summary of work carried out by the Woods Hole Oceanographic Institution under the following headings: Papers submitted for publication; Preliminary report on ATLANTIC Cruise 157; Deep water in the Brownson Deep; Oceanography of the Mediterranean Sea; Oceanographic surveys off East Coast of U.S. between Miami, Florida, and Cape Hatteras; Arctic oceanography; Salinity titrations and calibrations of thermometers; Sea surface wave investigations; Current measurments; Theoretical studies; Unattended oceanographic instruments; Assistance to Hydrographic Office; Assistance to the Naval Research Laboratory; Bathythermochronograph; Gulf Stream investigation - H.M.C.S. NEW LISKEARD; and Personnel.